Toward operationalizing deficient emotional self-regulation in newly referred adults with ADHD: A receiver operator characteristic curve analysis. Issue 1 (2020) - Biederman, Joseph; DiSalvo, Maura; Woodworth, K. Yvonne; Fried, Ronna; Uchida, Mai; Biederman, Itai; Spencer, Thomas J.; Surman, Craig; Faraone, Stephen V.
Abstract: Background: A growing body of research suggests that deficient emotional self-regulation (DESR) is common and morbid among attention-deficit/hyperactivity disorder (ADHD) patients. The main aim of the present study was to assess whether high and low levels of DESR in adult ADHD patients can be operationalized and whether they are clinically useful. Methods: A total of 441 newly referred 18- to 55-year-old adults of both sexes with Diagnostic and Statistical Manual of Mental Disorders: Fifth Edition (DSM-5) ADHD completed self-reported rating scales. We operationalized DESR using items from the Barkley Current Behavior Scale. We used receiver operator characteristic (ROC) curves to identify the optimal cut-off on the Barkley Emotional Dysregulation (ED) Scale to categorize patients as having high- versus low-level DESR and compared demographic and clinical characteristics between the groups. Results: We averaged the optimal Barkley ED Scale cut-points from the ROC curve analyses across all subscales and categorized ADHD patients as having high- ( N = 191) or low-level ( N = 250) DESR (total Barkley ED Scale score ≥8 or <8, respectively). Those with high-level DESR had significantly more severe symptoms of ADHD, executive dysfunction, autistic traits, levels of psychopathology, and worse quality of life compared with those with low-level DESR. There were no major differences in outcomes among medicated and unmedicated patients. Conclusions: High levels of DESR are common in adults with ADHD and when present represent a burdensome source of added morbidity and disability worthy of further clinical and scientific attention.